Impact of sex on management and survival in aortic stenosis. (25th November 2020) - Bohbot, Y; Rusinaru, D; Belkhir, K; Altes, A; Delpierre, Q; Serbout, S; Levy, F; Marechaux, S; Sarano, M; Tribouilloy, C
Abstract: Background: Increasing attention has been paid to differences between the sexes in recent studies, but only a few have focused on such differences in aortic stenosis (AS). Purpose: We sought to evaluate the differences between genders in AS outcomes and management. Methods: We included 2429 patients (51.5% men; 49.5% women) with severe AS. Median follow-up was 42.0 (21–78) months. Results: Women were older (p<0.001), more often symptomatic (p=0.007), and presented with smaller aortic valve area (p<0.001), and greater ejection fraction (p<0.001) than men. Despite that women have a longer life expectancy than men in the general population, estimated five-year survival of patients with severe AS was lower for women compared to men (62±2% versus 69±1% respectively, p<0.001). The 5-year survival was lower compared to expected survival, especially for women (62±2% vs. 71% for women and 69±1% vs. 71% for men). The cumulative 5-years incidence of AVR was 79±2% for men, and only 70±2% for women (p<0.001) and, being male was independently predictive of AVR (OR: 1.49 [1.18–1.97]; p=0.011). After propensity matching, when both genders were comparable in terms of characteristics and management (AVR), women, as expected due to their higher life expectancy than men, had better 5-year survival than men (69±2% vs. 62±2%; p=0.023). Conclusion: Women with severe AS present at a more advance stage of the disease, at older ages with more symptoms, and incur higher mortality than men. This excess mortality is related to a combination of late diagnosis and a less frequent and later referral for AVR than in men. This justifies appropriate measures to improve the situation and to ensure that both sexes receive equivalent care. Funding Acknowledgement: Type of funding source: None